THEORETICAL ASPECTS OF THE FORMATION OF ACCOUNTANT’S PROFESSIONAL COMPETENCE IN WORKING ENVIRONMENT - Beinarovica-Litvinova, Irena; Danilane, Liga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The last few years have seen significant changes in the world economy and by extension in accounting. Modern accountants have an important role in global entrepreneurship. As a result, the majority of employers prefer candidates with advanced accounting or auditing experience, knowledge of IT, including accounting and internal audit software, and good foreign language skills. The article contains an analysis of the content and components of the professional competence of accountants working in Latvia. The theoretical review is based on the information gathered and analysed from open sources and scientific databases.